PHOTOTHERAPY OUTCOMES AND BILIRUBIN ASSESSMENT TECHNIQUES IN PRETERM NEONATES: A TERTIARY CARE EXPERIENCE - MANTHALE, AISHWARAYA; DESAI, TRIVENI; KAMATH, RASHMI; GODI, VEERESH (International Journal of Current Pharmaceutical Research, 2025)
Objective: Management of neonatal jaundice, particularly in preterm neonates, is a significant challenge in neonatal care, with phototherapy serving as the primary treatment modality. This study evaluates the outcomes of phototherapy and the efficacy of different bilirubin assessment techniques in a tertiary care environment. Methods: A hospital-based prospective observational study was conducted involving 100 preterm neonates. Transcutaneous (TcB) and total serum bilirubin (TSB) levels were measured before, during, and after phototherapy to assess correlations and differences. Results: Statistically significant correlations were found between TcB and TSB post-phototherapy (r-value = 0.8154, p-value<0.0001) and during phototherapy (r-value = 0.6069, p-value<0.0001). However, TcB tended to underestimate bilirubin levels compared to TSB post-phototherapy, with a mean difference of -0.42 mg/dl (p-value = 0.0117). Conclusion: Despite discrepancies with traditional serum bilirubin (TSB) measurements during and after phototherapy, TcB proves to be an effective tool in clinical practice. The findings suggest that with further refinement and adjustment for influencing factors, TcB can serve as an equivalent to serum assessments, reducing the need for invasive procedures in neonatal jaundice management.